A companion to the philosophy of technology - Friis, Jan Kyrre Berg Olsen, 1963-; Pedersen, Stig Andur, 1943-; Hendricks, Vincent F. (Blackwell companions to philosophy., 2013)
Drawing on essays from leading international and multi-disciplinary scholars, A Companion to the Philosophy of Technology is the first comprehensive and authoritative reference source to cover the key issues of technology's impact on society and our lives. Presents the first complete, authoritative reference work in the fieldOrganized thematically for use both as a full introduction to the field or an encyclopedic referenceDraws on original essays from leading interdisciplinary scholarsFeatures the most up-to-date and cutting edge research in the interdisciplinary fie.